ENLARGED STARCH GRAIN1 affects amyloplast development and starch biosynthesis in rice endosperm. (April 2021) - Wang, Rongqi; Ren, Yulong; Yan, Haigang; Teng, Xuan; Zhu, Xiaopin; Wang, Yupeng; Zhang, Xin; Guo, Xiuping; Lin, Qibing; Cheng, Zhijun; Lei, Cailin; Wang, Jiulin; et al.
Highlights: esg1 shows floury grain appearance with altered starch physicochemical properties. Mutation in ESG1 leads to enlarged starch grains (SGs) in rice endosperm. ESG1 is homologous to the bacterial MlaE lipid transfer protein. ESG1 is localized to chloroplast and amyloplast membranes. Mutation of ESG1 causes defective galactolipid synthesis. Abstract: Cereal crops accumulate large amounts of starch which is synthesized and stored in amyloplasts in the form of starch grains (SGs). Despite significant progress in deciphering starch biosynthesis, our understanding of amyloplast development in rice ( Oryza sativa ) endosperm remains largely unknown. Here, we report a novel rice floury mutant named enlarged starch grain1 ( esg1 ). The mutant has decreased starch content, altered starch physicochemical properties, slower grain-ﬁlling rate and reduced 1000-grain weight. A distinctive feature in esg1 endosperm is that SGs are much larger, mainly due to an increased number of starch granules per SG. Spherical and loosely assembled granules, together with those weakly stained SGs may account for decreased starch content in esg1 . Map-based cloning revealed that ESG1 encodes a putative permease subunit of a bacterial-type ABC (ATP-binding cassette) lipid transporter. ESG1 is constitutively expressed in various tissues. It encodes a protein localized to the chloroplast and amyloplast membranes. Mutation of ESG1 causes defective galactolipid synthesis. The overall study indicates that ESG1 is a newly identified protein affecting SG development and subsequent starch biosynthesis, which provides novel insights into amyloplast development in rice.